2019
DOI: 10.1021/acs.energyfuels.9b01638
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-Tar-Enabled Nitrogen-Doped Highly Ultramicroporous Carbon as an Efficient Absorbent for CO2 Capture

Abstract: As a notorious hazardous waste, biomass tar has for a long time been recognized as one of the key challenges throughout the progress in biomass gasification for renewable energy and chemical purposes. In this contribution, we report that biomass tar featured with considerably high carbon and nitrogen contents could serve as an ideal source for production of nitrogen-doped highly ultramicroporous carbon following the facile activation approach, which enabled a remarkably high ultramicroporosity based on a direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The obtained C and N contents of the samples are also among the highest values reported in the literature. 1,2,10,29 On the contrary, the oxygen content has decreased during the HTC process due to the decomposition of the oxygenic groups upon heating, resulting in the formation of porous structures (Figure S2, Table S1; Supporting Information). However, the oxygen content of products is in the ideal range for the production CO 2 and H 2 O during physical and chemical activation procedures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained C and N contents of the samples are also among the highest values reported in the literature. 1,2,10,29 On the contrary, the oxygen content has decreased during the HTC process due to the decomposition of the oxygenic groups upon heating, resulting in the formation of porous structures (Figure S2, Table S1; Supporting Information). However, the oxygen content of products is in the ideal range for the production CO 2 and H 2 O during physical and chemical activation procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon emissions predominantly in the form of CO 2 are a major contributor to the greenhouse effect and climate change. Consequently, it has been a significant burden on the environment and human health on a global scale .…”
Section: Introductionmentioning
confidence: 99%
“…According to the IUPAC classication, the adsorption isotherms of PUPW-ACA and CS-ACA are Type I, while the adsorption isotherms of PC-ACA and AT-AC are Type IV. 27,[38][39][40][41] It was shown that micropore dominated in the PUPW-ACA and CS-ACA, while mesopore dominated in the PC-ACA and AT-AC, as supported by the microporosity in Table 1. AT and PC have high crystallinity, high degree of ordering, compact structure, and partial graphitization.…”
Section: Characterization Of Acasmentioning
confidence: 71%
“…The physical and chemical properties of the biochar surface directly affect the adsorption process of CO 2 molecules. The presence of heteroatoms (S, P, O, N, and halogen) is closely related to the chemical properties of the material surface. , These heteroatoms can not only exist in the precursor but also on the surface of the adsorbent and even be introduced in a series of ways during the reactivation process . The delocalized electrons of the carbon material matrix will interact with the functional groups brought by the heteroatoms, which will cause the chemical properties of the adsorbent surface to be changed (pH, adsorption, stability, etc.).…”
Section: Functional Modification Of Biocharmentioning
confidence: 99%
“…The atomic sizes of N and C atoms are almost the same because these atoms are easily assembled in a crystal lattice and replaced with each other, which makes multiple types of a simple structure. , The N doping of biochar is generally replaced by N atoms and part of C atoms to form N-containing functional groups (such as amine, nitro, nitroso, pyrrole, pyridine, etc.). At relatively low temperatures, pyridyl groups are preferentially formed on the carbon surface, and in the scope of 500–800 °C, pyrrole/pyridine nitrogen can be converted to pyridine nitrogen .…”
Section: Functional Modification Of Biocharmentioning
confidence: 99%